On‐resin microwave‐assisted copper‐catalyzed azide‐alkyne cycloaddition of H1‐relaxin B single chain 'stapled' analogues. Issue 4 (23rd March 2020) - D'Ercole, Annunziata; Sabatino, Giuseppina; Pacini, Lorenzo; Impresari, Elisa; Capecchi, Ilaria; Papini, Anna Maria; Rovero, Paolo
Abstract: The development of conformationally constrained analogues of bioactive peptides is a relevant goal in peptide medicinal chemistry. Among the several classes of conformationally constrained peptides, the so‐called stapled peptides, which bear a side‐chain‐to‐side‐chain bridge, are particularly interesting since they offer the possibility to stabilize specific conformational elements, such as α‐helices or β‐turns. We describe an efficient and reproducible microwave‐assisted strategy to prepare side‐chain‐to‐side‐chain clicked peptides, performing the copper‐catalyzed azide‐alkyne cycloaddition on solid phase, using as a model peptide a portion of the H1‐relaxin B chain, which contains the binding cassette motif of this important bioactive peptide. All the relevant parameters, that is, resin, solvent, catalytic system, microwave energy and reaction time were optimized using a systematic one‐factor‐at‐a‐time (OFAT) approach. This method will be useful for the preparation of libraries of conformationally constrained relaxin analogues. Abstract :